IMPROVING STUDENTS’ READING COMPREHENSION THROUGH TOP-DOWN STRATEGY - Muh. Syabri; Ammang Latif; Amaluddin Amaluddin (Universitas Muhammadiyah Makassar, 2021)
The objective of this research was to find out the improvement of the students’ reading comprehension by using Top-Down strategy in learning reading comprehension at SMA Negeri 1 Wajo. This research employed Pre-experimental method. The population of this research was eight classes of the Tenth grade students at SMA Negeri 1 Wajo in academic year 2019/2020 with the total population were 242 students. The researcher took random sampling and chosen X MIA 1. The data of the research were collected by using the instrument, namely reading test. The result of data analysis showed that there was significant difference between the students’ score after they were taught by top-down strategy and before they were taught by using top-down strategy. It was proved by the mean score of post-test was higher than the mean score of pre-test (67.2042.56). Furthermore, the result of the p- value (0.00) was lower than α (0.000.05) which meant that H1 was accepted.